1990
DOI: 10.1159/000263581
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Major Histocompatibility Complex Gene Products in Tissues Isolated from the Developing Human Nervous System

Abstract: We have examined the expression of the major histocompatibility complex (MHC) class I and II gene products in the developing human fetal peripheral nervous system. As determined by RNA blot hybridization analysis, MHC class I RNA was readily detectable in extracts prepared from dorsal root ganglia (DRG) obtained from aborted human fetal material. However, utilizing similar methodology, it was not possible to detect MHC class II RNA. In conjunction with these studies, expression of MHC class I and II proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…These studies have indicated that untreated human fetal DRG neural cell populations maintained in culture for a total of 5 days express a low level of MHC class II-specific RNA and protein. This observa tion further supports previous studies report ing MHC class II-specific protein, detectable only by FACS analysis but not by Western blot or RNA hybridization analyses [28], sug gesting a low level of MHC class II gene prod ucts in human fetal DRG neural cell popula tions which appears to be enhanced by pro longed in vitro cultivation. In addition, these findings are in agreement with studies per formed by other investigators in which low levels of MHC class II proteins were detect able on Schwann cells, satellite cells, and other resident cells of the central and periph eral nervous systems [50,51].…”
Section: Effect O F Y-ifn On the Accumulation O F Mhc Class I And Clasupporting
confidence: 90%
See 4 more Smart Citations
“…These studies have indicated that untreated human fetal DRG neural cell populations maintained in culture for a total of 5 days express a low level of MHC class II-specific RNA and protein. This observa tion further supports previous studies report ing MHC class II-specific protein, detectable only by FACS analysis but not by Western blot or RNA hybridization analyses [28], sug gesting a low level of MHC class II gene prod ucts in human fetal DRG neural cell popula tions which appears to be enhanced by pro longed in vitro cultivation. In addition, these findings are in agreement with studies per formed by other investigators in which low levels of MHC class II proteins were detect able on Schwann cells, satellite cells, and other resident cells of the central and periph eral nervous systems [50,51].…”
Section: Effect O F Y-ifn On the Accumulation O F Mhc Class I And Clasupporting
confidence: 90%
“…The assay was performed using serial dilutions of each RNA with the labeled RNA probe in excess (1X 106 cpm/ml) to allow for comparison of experimental results. As reported previously [28], untreated human fetal DRG neural cell populations contain a moderate level of MHC class I-specific RNA. However, as shown in Figure 2.…”
Section: Effect Ofy-ifn On Mhc Class I and Ii Rna Accumulation In Humsupporting
confidence: 78%
See 3 more Smart Citations